(untitled) (Journal of Asian Geography, 2023)
Being conscious of climate change is essential for emerging nations to attain sustainability. In developing countries, a major obstacle to adapting to climate change is a lack of awareness. This research, therefore, assesses the awareness of climate change impacts among Malaysians. The findings are based on an online survey conducted among citizens in Malaysia. The survey explores the level of awareness among Malaysians and their adaptation to face climate change. Based on the research, the highest mean score for awareness is 4.29 (agree–very agree), while the highest mean score for structure is 3.76 (neutral–agree). Even though the level of awareness is quite high among Malaysians, most of them believe that they and the government are not fully prepared to face climate change in Malaysia. It is recommended that the government strengthen the institutional setup to prepare and implement related climate change adaptation strategies in Malaysia.